2016
DOI: 10.4236/ojrad.2016.61005
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Stromal Tumors: Correlation of Multislice CT Findings to Histopathologic Features and Preliminary Validation of New Scoring System

Abstract: Purpose: The purpose of this study is to demonstrate the correlation between radiologic and pathologic features of the gastrointestinal stromal tumors. Patients and methods: A retrospective review from 2004 to 2014 identified 50 resected cases of confirmed gastrointestinal stromal tumors (GIST) is done. All these lesions were visualized in the first multi-slice computed tomography (MSCT) investigation. Radiologic and pathologic features were reviewed and compared. A radiologic score with MSCT findings was esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
1
0
1
Order By: Relevance
“…Our study has demonstrated that 89.5% of leiomyomas were located either in the cardioesophageal junction or the cardiac section of the stomach, which does not contradict the earlier findings in the literature and can be explained by close location to the esophagus, which is the most frequent localization site for leiomyomas [7]. In contrast to that, the most common localization site for GISTs is stomach, which also consistent with other studies [8,9].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study has demonstrated that 89.5% of leiomyomas were located either in the cardioesophageal junction or the cardiac section of the stomach, which does not contradict the earlier findings in the literature and can be explained by close location to the esophagus, which is the most frequent localization site for leiomyomas [7]. In contrast to that, the most common localization site for GISTs is stomach, which also consistent with other studies [8,9].…”
Section: Discussionsupporting
confidence: 91%
“…Напротив, наиболее распространенной локализацией ГИСО является тело желудка, что также согласуется с результатами других исследований [8,9].…”
Section: данные анализа кт-изображенийunclassified
“…11 To date, diagnosis of GIST is established by imaging as surgical biopsy for specimen carries on the risk of tumor rupture and tumor seeding along the tract of biopsy. 12 CT scan is reported to have a superiority in differentiating GIST to non-GIST as CT provides accurate tumor size, location, and tumor heterogeneity. 13 There's a group of experts believed that the accuracy of CT scan to be superior in diagnosing GIST, while as in contrast others recommend other modalities.…”
Section: Introductionmentioning
confidence: 99%